PENAMBATAN SENYAWA ANTIVIRUS PADA RESEPTOR NON STRUCTURAL PROTEIN SEBAGAI AGEN TERAPETIK COVID-19 - Saeful Amin; Risna Rosmiyati; Ade Yeni Aprilia; Salsabila Adlina; Andri Prasetiyo (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2023)
COVID-19 is a disease that attacks the human respiratory system, until now there is no medicine specifically recommended to treat COVID-19, but infected people should still get appropriate treatment to overcome the symptoms of COVID-19. Nsp10 plays an important role in viral transcription. The study aimed to look at the binding value of affinity, hydrogen bonds, and amino acid residues between antiviral compounds and Nsp 10 receptors. The methods used in this study are the molecular docking method using AutodockTools 1.5.6 program, and visualization of docking results using Discovery Studio Visualizer. Antiviral compounds used favipavir, remdesivir, chloroquine, oseltamivir, hydroxychloroquine, ribavirin, umifenovir, lopinavir and ritonavir. The receptors used in this study were 7L6T receptors. The analysis of docking results showed that umifenovir compounds have the lowest binding affinity compared to other antiviral compounds against 7L6T receptors of -6.43 kcal/mol, predictable to have more stable interactions. So that the umifenovir compound can be used as a candidate for COVID-19 treatment.